The effect of the rheocast process on the microstructure and mechanical properties of Al-5.7Si-2Cu-0.3Mg alloy - Abdelgnei, Mnel A H; Mohd Zaidi Omar,; Mariyam Jameelah Ghazali,; Mohamed A. Gebril,; M N Mohammed, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study shows the results of an experimental investigation of semisolid rheocasting of Al-5.7Si-2Cu-0.3Mg alloy using a cooling slope (CS) casting technique. However, the challenge is to determine process parameters of the CS process to get a desirable microstructure in the semisolid feedstock material. cooling slope technique was employed to create feedstock material for thixoforming under an argon gas atmosphere, where on an inclined plate that was fixed at a 60° slope angle, molten alloy is poured at different temperatures of 640°C, 650°C and 660°C at lengths 300, 400 and 500 mm. Examination the microstructure with optical microscope observed that the microstructure of conventionally cast alloy presented coarse and dendritic primary α-Al phase, whereas rheocast alloy included fine and nondendritic primary α-Al phase with homogeneous distribution of eutectic phase. The best CS processing condition has been identified for optimum pouring temperature of 650°C and the slope length of 400 mm as average globular grain size of around 31.67 ± 3 μm and a shape factor of about 0.66 ± 0.09 were obtained. The mechanical properties of conventional cast alloy were enhanced by the CS casting process. The ultimate tensile strength, the yield strength and elongation of the rheocast alloy were increased by 10%, 12% and 22% respectively compared to the conventional cast alloy. due to a reduction in shrinkage and porosity of the microstructure of the CS alloy.